An Analysis of The Principal’s Managerial Competence in Improving Teacher Performance - Mufaridun, Abdullah; Marmoah, Sri; Roemintoyo, Roemintoyo (Universitas Sebelas Maret, 2026)
This study aims to analyze the principal’s managerial competence in improving teacher performance by examining three main variables, namely X1 (planning ability), X2 (organizing ability), and X3 (supervisory ability). The research method employed is a quantitative descriptive approach, with data collection techniques including questionnaires, interviews, and documentation. The population of this study consists of all teachers at the school under investigation, while the sample is determined using purposive sampling techniques. The data are analyzed using multiple regression analysis to determine the effect of each variable X1, X2, and X3 on Y (teacher performance). The results of the study indicate that the three variables of the principal’s managerial competence have a positive and significant effect on improving teacher performance. The X1 variable (planning) provides the greatest contribution, followed by X2 (organizing) and X3 (supervision). This finding demonstrates that principals who are capable of developing strategic plans, effectively organizing school resources, and conducting continuous supervision can enhance teachers’ motivation and professionalism in carrying out their duties. Therefore, improving the principal’s managerial competence becomes a key factor in achieving optimal educational quality.